Packetcable implementation - Riddel, Jeff (Networking technology series., 2007)
PacketCable Implementation Design, provision, configure, manage, and secure tomorrow's high-value PacketCable networks Jeff Riddel, CCIE® No. 12798 PacketCable networks use IP technology to enable a wide range of multimedia services, from IP telephony to interactive gaming and beyond. Because PacketCable-based business and residential services are central to the cable industry's strategy for growth, the industry's need for PacketCable expertise is expected to increase dramatically. PacketCable Implementation is the first complete primer on PacketCable network design, provisioning, configuration, management, and security. Drawing on consulting experience with every leading cable operator, Jeff Riddel presents real-world case studies, sample network designs, configurations, and practical tips for all facets of PacketCable planning and deployment. This book's end-to-end coverage has been designed for cable engineers and networking professionals with widely diverse backgrounds and experience. Topics covered include PacketCable specifications and functional components, multimedia terminal adapters (MTA) provisioning, call signaling, media streaming, quality of service (QoS), event messaging, security, and much more. Every chapter contains tables and charts that serve as quick, easy references to key points. Each chapter closes with a summary and chapter review questions designed to help you assess and deepen your understanding. PacketCable Implementation brings together everything you need to know about cable networking to service delivery. Discover the PacketCable "big picture," including key application opportunities Learn about the latest generation of PacketCable standards and specifications, including PacketCable 2.0 and DOCSIS 3.0 Understand the functional components of a PacketCable network and how they fit together Walk step-by-step through provisioning, including protocols, flows, and MTA configuration Gain an in-depth understanding of call signaling: message formats, Network-based Call Signaling (NCS), PSTN interconnects, Call Management Server Signaling (CMSS), and more Implement efficient, high-performance media streaming Deploy, analyze, manage, and troubleshoot a state-of-the-art QoS framework Manage crucial network considerations, including lawful intercept Introduction Part I Introduction and Overview of PacketCable Chapter 1PacketCable Overview Chapter 2 PacketCable Functional Components Part II MTA Provisioning Chapter 3 Provision ...